Determination of factors affecting the development processes of active fencing referees in Turkey - Tuncay Sarıipek; Yusuf Barsbuğa (Ozlem Book Center, 2023)
The objective of this study is to determine and interpret the opinions of the fencing referees who are actively involved in the competitions in our country on the issues affecting their development processes. The study group; The Turkish Fencing Federation consists of 80 referees who are on the list of referees with a visa for 2021. An online data collection form was used as a data collection tool in this study, which was structured through the qualitative research method. In the analysis process of the data obtained, the data analysis program called MAXQDA Analyctis Pro (2022) was used. While closed-ended questions were summarized by indicating percentages, the content analysis method was used in the process of analyzing open-ended question and answer reports. The data obtained were visualized with the help of frequency tables and code maps. Finally, some of the opinions of the participants, which were coded, were directly conveyed by interpreting the findings obtained through the tables and code maps. As a result of the research, negative and positive views that affect the development processes of fencing referees in Turkey were categorized. While the issues such as training and development seminars organized for referees, increasing the number of referees' duties, meeting the accommodation and meal expenses of the referees, and improving their wages are among the positive factors; Factors such as the excessive working hours of the referees, the pressure of the coaches and athletes, the low wages, and the lack of sufficient job opportunities were evaluated within the scope of negative effects.